The impact of social media on young people’s self-esteem, body image and mental health - Diljá Sturludóttir 1995- (2020)
There have been significant changes in the western world with the advent of social media. Recent studies have indicated that social media can have a wide impact on young adult’s self-esteem, body image and mental health. Adolescents and young adults are the generation that use social media the most. This age group is particularly vulnerable when it comes to the harmful effects from social media. The impact of social media has been a popular research topic in recent year. However, the current study aims to explore the effect of social media on the self-esteem, body image and mental health of high school students in Iceland. A questionnaire from Rannsókn og Greining (R&G) from 2018 was used to collect the data. Icelandic high school students (N = 2072) from all over the country answered the survey, 49,3% males and 48,9% females. The results showed that excessive social media usage has a negative effect on young people’s self-esteem, body image and mental health. Keywords: social media, self-esteem, body image, mental health. Gríðarlegar breytingar hafa orðið í vestrænum heimi með tilkomu samfélagsmiðla. Fjöldi rannsókna hafa sýnt að áhrif samfélagsmiðla á sjálfstraust, líkamsímynd og andlega heilsu ungs fólks geti verið víðtæk. Ungt fólk og unglingar eru sú kynslóð sem notar samfélagsmiðla mest. Þessi aldurshópur er sérstaklega viðkvæmur þegar kemur að slæmum áhrifum samfélagsmiðla. Áhrif samfélagsmiðla hefur verið vinsælt rannsóknarefni síðustu ár. Markmið þessarar rannsóknar er þó að kanna hvernig samfélagsmiðlar geti haft áhrif á sjálfstraust, líkamsímynd og andlega heilsu meðal framhaldsskólanema á Íslandi. Spurningalisti frá Rannsókn og Greining (R&G) frá 2018 var notaður til gagnaöflunar. Íslenskir framhaldsskólanemar (N = 2072) víðsvegar um landið svöruðu könnuninni, 49,3% drengir og 48,9% stúlkur. Niðurstöðurnar sýndu að of mikil samfélagsmiðlanotkun hafi neikvæð áhrif á sjálfstraust, líkamsímynd og andlega líðan meðal ungs fólks. Leitarorð: samfélagsmiðlar, sjálfstraust, líkamsímynd, andleg ...